Perlindungan Konsumen terhadap Hak Atas Informasi Harga Pada Menu Makanan, dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen (Studi Kasus di Warung Makan pada Kawasan Malioboro) - Lindra & Wiji Darnela & Saraspeni (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
This study concluded that the implementation of consumer protection for the right to update the prices on the food menu, food stall at Malioboro area is not in accordance with the Act 8 of 1999 on Consumer Protection. Based on observations in the field, the consumer does not get its due in the form of pricing information which should be given by most businesses in the area of malioboro. In this case most businesses in the area of Malioboro has violated its obligations as entrepreneurs. it is evident from as regulated in Article 7 butur b Law No. 8 of 1999 on Consumer Protection explained that the obligation of the consumer is "Providing accurate information, clear, honest, on the condition and guarantee of the goods and / or services and to give explanations use, repair and maintenance ".